High Fat Diet Induces Liver Steatosis and Early Dysregulation of Iron Metabolism in Rats - Meli, Rosaria; Mattace Raso, Giuseppina; Irace, Carlo; Simeoli, Raffaele; Di Pascale, Antonio; Paciello, Orlando; Pagano, Teresa Bruna; Calignano, Antonio; Colonna, Alfredo; Santamaria, Rita (PLOS ONE, 2013)
This paper is dedicated to the memory of our wonderful colleague Professor Alfredo Colonna, who passed away the same day of its acceptance. Fatty liver accumulation, inflammatory process and insulin resistance appear to be crucial in non-alcoholic fatty liver disease (NAFLD), nevertheless emerging findings pointed an important role also for iron overload. Here, we investigate the molecular mechanisms of hepatic iron metabolism in the onset of steatosis to understand whether its impairment could be an early event of liver inflammatory injury. Rats were fed with control diet or high fat diet (HFD) for 5 or 8 weeks, after which liver morphology, serum lipid profile, transaminases levels and hepatic iron content (HIC), were evaluated. In liver of HFD fed animals an increased time-dependent activity of iron regulatory protein 1 (IRP1) was evidenced, associated with the increase in transferrin receptor-1 (TfR1) expression and ferritin down-regulation. Moreover, ferroportin (FPN-1), the main protein involved in iron export, was down-regulated accordingly with hepcidin increase. These findings were indicative of an increased iron content into hepatocytes, which leads to an increase of harmful free-iron also related to the reduction of hepatic ferritin content. The progressive inflammatory damage was evidenced by the increase of hepatic TNF-α, IL-6 and leptin, in parallel to increased iron content and oxidative stress. The major finding that emerged of this study is the impairment of iron homeostasis in the ongoing and sustaining of liver steatosis, suggesting a strong link between iron metabolism unbalance, inflammatory damage and progression of disease.